Antibacterial gold nanoparticle-based photothermal killing of vancomycin-resistant bacteria. (4th July 2018) - Wang, Sin-Ge; Chen, Yen-Chun; Chen, Yu-Chie
Aim: The extensive use of vancomycin has given rise to vancomycin-resistant bacterial strains, such as vancomycin-resistant Enterococci (VRE). We aim to explore potent medical treatments that can inhibit the growth of VRE.Materials & methods: Vancomycin-immobilized gold nanoparticles (Au@Van NPs) with polygonal shapes from one-pot reactions were generated within approximately 7 min.Results & discussion: The as-prepared Au NPs exhibit not only antibacterial capability but also photothermal competence. The temperature of the sample solution containing the as-prepared Au@Van NPs can be raised by approximately 15°C under irradiation by a near-infrared laser (λ = 808 nm) within 5 min.Conclusion: The required amount of vancomycin on the as-prepared Au@Van NPs combined with near-infrared irradiation for inhibiting VRE is approximately 16-fold lower than that of free-form vancomycin.